Cause of death and excess mortality in patients with lower‐risk myelodysplastic syndromes (MDS): A report from the European MDS registry. (6th November 2022) - Mądry, Krzysztof; Lis, Karol; Fenaux, Pierre; Bowen, David; Symeonidis, Argiris; Mittelman, Moshe; Stauder, Reinhard; Čermák, Jaroslav; Sanz, Guillermo; Hellström‐Lindberg, Eva; Langemeijer, Saskia; Malcovati, Luca; et al.
Summary: Information on causes of death (CoDs) and the impact of myelodysplastic syndromes (MDS) on survival in patients with lower‐risk MDS (LR‐MDS) is limited. A better understanding of the relationship between disease characteristics, clinical interventions and CoDs may improve outcomes of patients with LR‐MDS. We prospectively collected data on patients with LR‐MDS in the European MDS registry from 2008 to 2019. Clinical, laboratory and CoDs data were obtained. To examine MDS‐specific survival, relative survival (RS) was estimated using national life tables. Of 2396 evaluated subjects, 900 died (median overall survival [OS]: 4.7 years; median follow‐up: 3.5 years). The most common CoDs were acute myeloid leukaemia/MDS (20.1%), infection (17.8%) and cardiovascular disease (CVD; 9.8%). Patients with isolated del(5q) and with red cell transfusion needed during the disease course, had a higher risk of fatal CVD. The 5‐year OS was 47.3% and the 5‐year RS was 59.6%, indicating that most patients died due to their underlying MDS. Older patients (aged >80 years) and the lowest‐risk patients were more likely to die from competing causes. This study shows that MDS and its related complications play crucial role in the outcome of patients with LR‐MDS.